Insertion of Costa Rica in global value chains: A case study - Ricardo Monge-González; Sandro Zolezzi (Inter-American Development Bank (IDB), 2012)
This study sheds light on how Costa Rica's insertion in global value chains occurs by examining governance patterns, the type of activities involved, and the level of underlying innovation in the selected value chain. The paper describes in detail two case studies of electronic-related companies in the aeronautic GVC that operate in Costa Rica as suppliers of global players in this industry. The final objective of the research is to contribute to the understanding of how public policies can be employed to improve Costa Rica's exporting and innovating performance.
hdl:11319/4256
Keywords: F14; F23; 330; Global Supply Chains; International Fragmentation of Production; Suppliers